Depression and suicidal ideation among dental students of Southern Saudi Arabia: A cross sectional study. Issue 12 (20th August 2021) - Almoammar, Salem; Alqarni, Kholod Abdurhman; Alnazeh, Abdullah A.; Alshahrani, Razan Mohamed; Sundram, Frederick; Alyami, Mohsen; Alyami, Hussain
Abstract: Purpose: To assess depression and suicidal ideation among dental students at King Khalid University College of Dentistry, Abha, Saudi Arabia. Methods: A cross‐sectional questionnaire‐based study was carried out among dental students between January and March 2020. The Arabic version of the Patient Health Questionnaire (PHQ‐9) was used to assess depression, while suicidal ideation was assessed using three questions related to suicidal behaviors drawn from the literature. Results: A total of 218 participants completed the questionnaires. More than 40% of the participants experienced depression while the prevalence of suicidal ideation was 48.2%; around a third of the sample had suicidal ideation, and half of which made a suicidal attempt in the preceding year ( p < 0.05). There was a lack of association between depression severity and suicidal ideation. Conclusion: A large proportion of dental students experienced depression and suicidal ideation. These findings invite in depth analysis of the causative and contributing factors for such high rates as well as ways for addressing them.